2008
DOI: 10.1002/anie.200703753
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Tyrosyl Biradical in Mouse R2 Ribonucleotide Reductase from High‐Field PELDOR

Abstract: Paramagnetic centers rigidly embedded in proteins serve as a probe in structural studies of macromolecular complexes. Pulse EPR at high frequencies allows the determination of not only the distance but also the relative orientation of these centers (see tyrosyl radicals; C gray, O red, N blue). The method has considerable potential for studying the assembly of protein complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 26 publications
0
46
0
Order By: Relevance
“…However, in the case of orientation selection and correlated orientations of the two radicals the modulation depth k depends on the orientation selected by the observer and pump pulses and by the relative orientation of the g-tensors [9,10,12]. DEER measurements were carried out with two pulse settings.…”
Section: Deer Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the case of orientation selection and correlated orientations of the two radicals the modulation depth k depends on the orientation selected by the observer and pump pulses and by the relative orientation of the g-tensors [9,10,12]. DEER measurements were carried out with two pulse settings.…”
Section: Deer Measurementsmentioning
confidence: 99%
“…In the last decade numerous applications of high field CW EPR and ENDOR have been reported and the virtues of measurements at a high field have been well demonstrated and established [1][2][3][4][5][6]. Recently, it has also been demonstrated that distance measurements between paramagnetic centers by pulsed DEER techniques can also be performed at high fields [9][10][11][12]. Distance measurements have become very popular in the last few years and are carried out usually at X-band frequencies [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second case corresponds to those time traces for which only certain orientations of the spin-spin vector r relative to the external magnetic field B 0 were excited. Examples for such a case are the tyrosine radicals in the ribonucleotide reductase dimer [9,10], the rigid spin label Ç in oligonucleotides [11,12], spin labels restricted in their rotational freedom by the protein environment [13,14] or transition metal * Corresponding author. Email: schiemann@pc.uni-bonn.de ions/clusters [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most important is the pulsed electron-electron double resonance technique (PELDOR, also called DEER), which allows measurement of long range distances (2-8 nm) between two paramagnetic species in macromolecules [1][2][3][4][5][6]. At high magnetic fields, PELDOR experiments can also deliver information about the relative orientations of paramagnetic species [7][8][9][10][11][12][13]. This is a valuable information to study conformational changes of macromolecules or assemblies of protein complexes in which paramagnetic centers are rigidly embedded.…”
Section: Introductionmentioning
confidence: 99%